2020
DOI: 10.2196/19093
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Known Barriers—Assessing Physician Perspectives and Attitudes Toward Introducing Open Health Records in Germany: Qualitative Study

Abstract: Background Giving patients access to their medical records (ie, open health records) can support doctor-patient communication and patient-centered care and can improve quality of care, patients’ health literacy, self-care, and treatment adherence. In Germany, patients are entitled by law to have access to their medical records. However, in practice doing so remains an exception in Germany. So far, research has been focused on organizational implementation barriers. Little is known about physicians’… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
(57 reference statements)
0
7
0
1
Order By: Relevance
“…A reason for this could be the fact that drug trough levels were transferred to the app automatically while physician’s letters were released manually. HCPs emphasized that this preselection of documents was important to avoid the risk of overburdening patients, which is a common concern [ 4 , 18 , 40 , 41 , 42 ]. However, whether the inconsistent availability of physician’s letters in app stemmed from technical issues or selective release remained unclear in this study and requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A reason for this could be the fact that drug trough levels were transferred to the app automatically while physician’s letters were released manually. HCPs emphasized that this preselection of documents was important to avoid the risk of overburdening patients, which is a common concern [ 4 , 18 , 40 , 41 , 42 ]. However, whether the inconsistent availability of physician’s letters in app stemmed from technical issues or selective release remained unclear in this study and requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Although entitled by national law in Germany, only a few patients access information stored in electronic health records (EHR) [ 18 , 19 ]. At the Heidelberg University Hospital, Heidelberg, Germany, the prerequisite for a patient-accessible medical record was met by implementing a web-based personal, cross-institutional health record, named “PEPA”, in 2016 [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“… 15 , 16 While research has demonstrated innumerable benefits when notes are openly shared with patients, 4 , 5 , 17 the notion that providing this access will do more harm than good for patients receiving psychiatric care prevails. 18 , 19 A variety of OpenNotes implementation resources have been developed for U.S. contexts; however, these have had limited applicability to Canadian environments. To bridge this gap, tailoring implementation strategies to the Canadian psychiatric environment is needed to enhance uptake of OpenNotes.…”
Section: Introductionmentioning
confidence: 99%
“…Inviting patients as yet another audience member through "open notes" signifies a new era in health care and health technology.Since the original open notes study in 2010, 14 patient access to electronic notes has increased worldwide and is now nearly universal in the United States. 2,6,15,16 Patients want to read their notes, 17 are learning from them, 18,19 and report several benefits, including increased participation in care. 14 Research shows that patient engagement is associat-ed with better outcomes and lower costs, 14,20-23 but sharing visit notes also raises clinician anxiety and concerns about patient worry.…”
mentioning
confidence: 99%
“…14 Research shows that patient engagement is associat-ed with better outcomes and lower costs, 14,20-23 but sharing visit notes also raises clinician anxiety and concerns about patient worry. 14,16,21,22,[24][25][26] Clinicians need low-burden, high-impact strategies for writing patient-centered notes that uphold communication between clinicians.Most note-writing guides to date have focused on the experience of clinicians. 27 Here, we build on these tips by integrating patient perspectives related to note-reading.…”
mentioning
confidence: 99%